PENDIDIKAN HUMANISTIK DALAM BELAJAR - Anwar, Bakri (Universitas Islam Negeri Alauddin Makassar, 2020)
Learning cannot be separated from human life. However, each of the human beings learn differently and will need different approaches. One of the interesting learning approaches is humanistic approach. This particular approach focuses on the students. It is assumed that students are the first and the main actors in education. The students are the subjects which become the center of attention in all educational activities. Humanistic educators believe that students have potentials, abilities, and strengths to develop. Education should not only focus on physical and intellectual but social and affective aspects of the students. This writing aims to describe humanistic approach and its learning activities in detailed.